Aliran Teologi Ahl Al-Hadits - Imam Bukhori (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Abstract This study discusses the flow of Ahl Al-Hadith theology that leads to the Salafiyah movement. The biggest basis is to have to hold on to al-Ma'usur wa-Manqul (religious texts, both hadith and Al-Qur'an). This is an argument that the majority of the people adhere to. He gave strength to the Salaf to oppose their enemies, namely, the atheists, extremists and reformers. The Salaf have ideas about the oneness of Essence, Ta'wil and Tafwidh and the oneness in creation. The teachings of Ahl Hadith that they reject ta'wil, philosophy and science of kalam. The Qur'an which in their view is worthy as the main guide for Muslims. In a contemporary sense, it refers to a reform movement. The term Ahl al-Hadith is often used interchangeably with the term Salafi and they prefer to call themselves Salafis, although they are often called Wahhabis with their enemies.   Keywords: flow of Ahl Al-Hadith, theology